1958
DOI: 10.1021/ja01553a016
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Catalysis of Hydrolytic Reactions. III. Intramolecular Catalysis by Carboxylate Ion in the Hydrolysis of Methyl Hydrogen Phthalate1,2

Abstract: cago through whose courtesy the mass spectrometer under AEC Contract At(ll-1)92 was made available. We thank the Simonize Co. for its contribution to the departmental fund for research.Chicago 16, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…In the literature, there are some early reports about the "acid anhydride" character of aspirin, [22] confirmed by other authors who claimed the anhydride intermediate was involved in the mechanism of hydrolysis of aspirin to acetic acid and salicylate. [23] However, later independent works by Fersht, [24] Jencks [25] and Kemp [26] demonstrated through elegant experiments that, while aspirin can actually exist in the anhydride form, the latter is not involved in the mechanism of solvolysis (either by water or alcohols), which instead proceeds under intramolecular general base catalysis provided by the vicinal carboxylate moiety (Scheme 1). The anhydride intermediate is thought not to play a role in solvolysis of aspirin because the greater nucleophilicity of the phenoxide anion with respect to solvent favors the intramolecular reaction reforming aspirin.…”
mentioning
confidence: 99%
“…In the literature, there are some early reports about the "acid anhydride" character of aspirin, [22] confirmed by other authors who claimed the anhydride intermediate was involved in the mechanism of hydrolysis of aspirin to acetic acid and salicylate. [23] However, later independent works by Fersht, [24] Jencks [25] and Kemp [26] demonstrated through elegant experiments that, while aspirin can actually exist in the anhydride form, the latter is not involved in the mechanism of solvolysis (either by water or alcohols), which instead proceeds under intramolecular general base catalysis provided by the vicinal carboxylate moiety (Scheme 1). The anhydride intermediate is thought not to play a role in solvolysis of aspirin because the greater nucleophilicity of the phenoxide anion with respect to solvent favors the intramolecular reaction reforming aspirin.…”
mentioning
confidence: 99%
“…This mechanism has been set out in its most acceptable form by Bender (Scheme 1) [9]. This hypothesis was supported by the same authors [10], which showed that a small amount of labelled oxygen from solvent 18 2 H O appears in the salicylic acid produced. Only Garrett has seriously questioned this mechanism.…”
Section: Introductionmentioning
confidence: 80%
“…The data in 'rable VI reveal that there is little or no' reaction of fumaramic acid with cellulose under the reaction conditions used (samples [1][2][3][4]. Maleamic acid, under the same conditions and the same concentration (samples 5b, 6b), give significant reaction, with DS values of 0.07 and 0.08, respectivelv.…”
Section: Ester Bond To a Cid And Basementioning
confidence: 97%
“…How can these stabilities . [2] have shown that the hydrolysis of methyl hydrogen phthalate occurs through intramolecular catalysis by the carboxytate ion. Therefore, at pH 2.0 -2.5, the ester bonds formed should be stable to hydrolysis since the unesterified carboxyl groups are non-ionized.…”
Section: Stability Of Ester Bonds Formed To Acidic and Basicmentioning
confidence: 99%